Needs Analysis of Clean Water to Improve the Health and Safety of the Pantai Sederhana Village Society, Muara Gembong - Catur Setyawan Kusumohadi; Adi Tri Tyaasmadi; Imam Basori; Jafar Amiruddin; Himawan Hadi Sutrisno; Triyono; Pratomo Setyadi; Fransisca Maria Farida (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract This community service activity was conduct to estimated the needs of clean water to improve the health and safety of the people of Pantai Sederhana Village. A preliminary study approach was carried out involving a survey of the health and safety conditions of the community regarding the quality of available water. This step also includes data analysis to understand the prevalence of water-related diseases. Furthermore, through active community participation, further information was obtained about their experiences and perceptions of the availability of clean water. From the results of the analysis of clean water needs, appropriate solutions will be designed, including infrastructure development and providing training to the community on maintaining clean water systems. Monitoring and evaluation will be carried out regularly to assess the effectiveness of the solutions implemented, while continuing to strengthen community capacity in terms of awareness of the importance of clean water for health and safety. Keywords: clean water, health, safety Abstrak Artikel kegiatan pengabdian masyarakat ini merupakan bagian dari kegiatan pembuatan alat penjernih air untuk masyarakat di Pantai Sederhana, Muara Gembong. Untuk dapat merencanakan ukuran dan kapasitas alat penjernih air yang sesuai, maka perlu dilakukan perhitungan kebutuhan air bersih yang diperlukan untuk meningkatkan kesehatan dan keselamatan masyarakat Desa Pantai Sederhana. Pendekatan studi pendahuluan dilakukan dengan melakukan survei terhadap kondisi kesehatan dan keselamatan masyarakat terkait kualitas air yang tersedia. Langkah ini juga mencakup analisis data untuk memahami prevalensi penyakit yang berhubungan dengan air. Selain itu, melalui partisipasi aktif masyarakat, diperoleh informasi lebih lanjut mengenai pengalaman dan persepsi mereka terhadap ketersediaan air bersih. Dari hasil analisis kebutuhan air bersih akan dirancang solusi yang tepat, antara lain pembangunan infrastruktur dan pemberian pelatihan kepada masyarakat tentang pemeliharaan sistem air bersih. Kata Kunci: air bersih, kesehatan, keselamatan